Characterization of complete mitochondrial genome of Yunnanilus jinxiensis (Cypriniformes, Balitoridae, Nemacheilidae) - Wei Huang; Guofan Shi; Anyou He; Yanhong Wen; Jie Huang; Fuguang Luo (Mitochondrial DNA. Part B. Resources, 2019)
Yunnanilus jinxiensis is an endemic cave-dwelling loach that only lives in the karst cave of Jingxi and Tiandong county, Southwestern China. The complete mitochondrial genome is 16,561 bp in length, consisting of 37 genes coding for 13 proteins, two rRNAs, 22 tRNAs, and one control region. Phylogenetic analysis using mitochondrial genomes of 14 species showed that Yunnanilus is mainly related to the genus Orenectes.